A New Approach to Improve TCP Performance over Asymmetric Networks - Al-Khatib, Wissam; Gunavathi, K. (Elektronika ir Elektrotechnika, 2006)
TCP performance issues in bandwidth asymmetric networks are investigated. Related works to improve TCP performance in bandwidth asymmetric networks are introduced and analyzed. A new approach to improve TCP performance in two way traffic over asymmetric networks is also proposed in this paper, which can further improve TCP performance by assigning the bandwidth rates over the reverse link dynamically. Simulation results show that the new scheme has better performance compared to existing algorithms in terms of good utilization of the existing resources and higher throughput. Ill. 7, bibl. 9 (in English; summaries in English, Russian and Lithuanian).